How public confidence was established during the COVID-19 pandemic by Chinese media: A corpus-based discursive news value analysis - Chen, Cheng; Liu, Renping (Frontiers in Public Health, 2022)
During the COVID-19 pandemic, Chinese media played a significant role in dispelling the public panic, establishing the public confidence and stabilizing the society during the COVID-19 pandemic. This corpus-based discourse study explored the discursive construction of news values by Chinese media to reveal how the COVID-19 pandemic was packaged and sold to the public to establish confidence in the news reporting. Adopting corpus linguistic method and the Discursive news values analysis (DNVA) framework, this study examines news values through key words, news quotations, and images in the Chinese domestic mainstream media (http://www.people.com.cn/) during two different phases of the pandemic. The results show that during the first pandemic phase (2019.12.27–2020.4.28) when there had been no treatment protocol or understanding of the medical ramifications, Chinese media dominantly constructed political Eliteness through multimodal resources to portray a people-oriented government, a transparent notification mechanism and an immediate response capability to crises, and to give the public psychological support and to cultivate positive attitudes toward the government's policy. This news reporting way exposes the universal trust of Chinese society in the political authorities. During the second phase (2020.4.29–2020.8.31) when the cognition about the COVID-19 virus had been greatly improved and more medical treatment and prevention methods had been developed, the political Eliteness was replaced by medical Eliteness which was more vital to people's safety during the health crisis. We propose actionable recommendations for scholars to use this in-depth DNVA framework to examine the social trend of thoughts during major public health crisis.